Potential of Trichoderma asperellum as biological control agent against black pepper anthracnose pathogens / Nur Ain Syuhada Saidi - Saidi, Nur Ain Syuhada (Faculty of Plantation and Agrotechnology, 2019)
Black pepper (Piper nigrum) is one of the oldest and popular spices in the world and widely cultivated in tropical regions. The major producer of black peppers are Indonesia, Vietnam, Malaysia and Brazil. Other than been infested by pest, black pepper also has been attacked by many diseases such as anthracnose, leaf blight, blight and root rot. The use of chemical fungicide to control plant disease is an integral component of plant disease management. However, a heavy usage chemical has led to many problems and constraints such as development of fungicide resistances. Therefore the objective of this study is to identify the effectiveness of Trichoderma asperellum as biocontrol agent against fungal pathogen associated with black pepper anthracnose disease using dual culture method. In this study, two species were identified as pathogen of black pepper anthracnose which are Colletotrichum spp. and Fusarium spp. Antagonistic study using dual culture technique showed that Trichoderma asperellum has great potential to suppress the growth of Colletotrichum spp. and Fusarium spp. This finding reveals that Trichoderma asperellum has a great potential to become a biological agents against black pepper anthracnose pathogen.